Analysis of Economic Growth in the Maritime Tourism Sector in Wakatobi Regency - Karto*, Armiyani; Trisetyasi, Evi; Ifianto, Ifianto (Universitas Syiah Kuala, 2023)
The maritime tourism sector is one sector that has the potential to increase economic growth in Wakatobi Regency. However, it is felt that the popularity of tourism in Wakatobi Regency has decreased somewhat, if seen from the Central Statistics Agency data on foreign tourism visits from year to year. This research aims to determine the influence of the variables Number of Foreign Tourists, Number of Domestic Tourists, Number of Tourist Attractions, Number of Hotel Rooms/Room Occupancy Rate on the Economic Growth of Wakatobi Regency in 2013 - 2022. The research uses secondary data with a sample of 10 years obtained from BPS Wakatobi Regency. The data analysis used is multiple linear regression analysis using SPSS 22 for Windows software. Hypothesis testing uses the F test, T test, and determination test. The research results show that simultaneously the variables Number of Foreign Tourists, Number of Domestic Tourists, Number of Tourist Attractions, Number of Hotel Rooms/Room Occupancy Rate have a significant effect on the Economic Growth of Wakatobi Regency. Meanwhile, partially the variables Foreign Tourists, Number of Tourist Attractions, Number of Hotel Rooms/Room Occupancy Rate have no significant effect on Economic Growth. Meanwhile, the Domestic Tourist variable has a positive and significant effect on the Economic Growth of Wakatobi Regency.